Modelling molecular structure and reactivity in biological systems - Naidoo, Kevin J. (Special publication (Royal Society of Chemistry (Great Britain)) ;, 2006)
This product is not available separately, it is only sold as part of a set. There are 750 products in the set and these are all sold as one entity.